Effect of meningitis and probenecid on the penetration of vancomycin into cerebrospinal fluid in rabbits. - Krontz, D P (1980)
This study examined the effects of experimental pneumococcal meningitis and probenecid administration on the penetration of parenterally administered vancomycin into cerebrospinal fluid in rabbits. Bacterial killing was also examined in infected animals. Meningitis was induced by intracisternal inoculation of Streptococcus pneumoniae. Vancomycin was administered in a loading dose followed by a continuous intravenous infusion for 6 h. Serum and cerebrospinal fluid samples were obtained at 0, 2, 4, and 6 h for antibiotic assays and quantitative cultures. Meningitis significantly enhanced the penetration of vancomycin into cerebrospinal fluid, but probenecid administration had no effect. In normal rabbits, at 6 h the mean percent penetration (cerebrospinal fluid concentration/serum concentration x 100%) +/- the standard deviation was 1.9 +/- 0.9% in the nonprobenecid group (n = 10) and 1.9 +/- 1.1% in the probenecid group (n = 9). In rabbits with experimental pneumococcal meningitis, the mean percent penetration at 6 h was 3.9 +/- 2.6% in the nonprobenecid group (n = 11) and 4.3 +/- 2.1% in the probenecid group (n = 9). Mean bacterial titers in the cerebrospinal fluid of infected animals decreased by more than 3.0 log 10 colony-forming units per ml in both the nonprobenecid and the probenecid groups.